Efektivitas Manajemen Sumber Daya Manusia Dalam Peningkatan Mutu Pendidikan di MTS: Sebuah Studi Kualitatif - Fajar, Abdul (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This study investigates the implementation of human resource management (HRM) in enhancing the quality of education at MTs YLPI Ibaadurrahman, focusing on integrating Islamic values into the management system. The objective is to evaluate how effectively HRM practices are aligned with educational goals and the community's expectations. Using a qualitative descriptive approach, the research gathered data through in-depth interviews, observations, and document analysis. The research design centered on understanding the impact of HRM practices on educational quality and spiritual development within a madrasah setting. Key findings reveal that HRM at MTs YLPI Ibaadurrahman has successfully improved the educational environment by promoting both academic and spiritual growth among staff and students. However, challenges remain in fully integrating Islamic values into HR management, particularly in performance evaluation and professional development. These findings contribute to the literature by highlighting the importance of contextualizing HRM in religious-based educational institutions. The study suggests that future research could explore mixed-method approaches to quantitatively assess the impact of HRM on educational outcomes. Limitations include the scope of the study, which was confined to one institution, and the reliance on qualitative data, which may limit generalizability. The implications of this research extend to broader educational management practices in Islamic institutions globally.